2011
DOI: 10.5600/mmrr.001.04.a01
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Medical Education and Disproportionate Share Adjustments to Medicare Inpatient Payment Rates

Abstract: The indirect medical education (IME) and disproportionate share hospital (DSH) adjustments to Medicare's prospective payment rates for inpatient services are generally intended to compensate hospitals for patient care costs related to teaching activities and care of low income populations. These adjustments were originally established based on the statistical relationships between IME and DSH and hospital costs. Due to a variety of policy considerations, the legislated levels of these adjustments may have devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…33 Federal regulators have subsequently allowed hospitals to expand the definition of community benefits to include research and health professions training programs—even when such activities are adequately compensated by Medicare and grant payments. 34 A handful of states specify minimum criteria—often tied to the level of care provided to uninsured and underinsured individuals—that hospitals must fulfil to retain property tax exemptions. 35 The low levels of care for Medicaid and uninsured patients reported by some AMCs in NYC (10% or less at one-third of them in 2014; data not shown) raises questions about the appropriateness of their claim to be providing substantial community benefits.…”
Section: Discussionmentioning
confidence: 99%
“…33 Federal regulators have subsequently allowed hospitals to expand the definition of community benefits to include research and health professions training programs—even when such activities are adequately compensated by Medicare and grant payments. 34 A handful of states specify minimum criteria—often tied to the level of care provided to uninsured and underinsured individuals—that hospitals must fulfil to retain property tax exemptions. 35 The low levels of care for Medicaid and uninsured patients reported by some AMCs in NYC (10% or less at one-third of them in 2014; data not shown) raises questions about the appropriateness of their claim to be providing substantial community benefits.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, each hospital's DGME payment is based substantially on the costs it reported in FYs 1984–1985, adjusted for inflation (Eden, Berwick, and Wilensky ). Likewise, the rules for calculating the DSH adjustment allow for a number of discontinuities, such as a ceiling of 0.12 for urban hospitals with up to 100 beds, but no ceiling for urban hospitals with 101 or more beds (Nguyen and Sheingold ).…”
Section: Discussionmentioning
confidence: 99%
“…). Separately, research by the MedPAC and others has raised concerns that payment adjustments, while in principle legitimate, are too large in the aggregate and poorly correlated with hospitals’ resource needs (Nguyen and Sheingold ; Chandra, Khullar, and Wilensky ; Grover, Slavin, and Willson ). MedPAC found that “at most, 25 percent of the DSH payments [were] empirically justified by the higher Medicare costs at hospitals treating low‐income patients” (MedPAC ) and that the $6.5 billion spent annually on IGME exceeds by $3.5 billion, the true added costs of teaching inpatient care (MedPAC ).…”
mentioning
confidence: 99%
“…One recent study indicated that current indirect medical education levels are 2 to 3 times as large as what would be an "empirically justified" level. 24,25 Given that the ACA does not include any indirect medical education cuts, university ownership may continue to provide some safety net hospital systems with a financial buffer as Medicaid DSH funds decline substantially over the next 5 years.…”
Section: Discussionmentioning
confidence: 99%